The performance of STRONGkids in the early detection of hospital malnutrition - Tommy Tommy; Herlina Dimiati; Mars Nasrah Abdullah; Sulaiman Yusuf; Teuku Muhammad Thaib; Rusdi Andid; Eka Destianti Edward (Indonesian Pediatric Society, 2022)
Background Hospital malnutrition in children can increase morbidity and mortality, regardless of the type of illness. The Screening Tool for Risk on Nutritional Status and Growth (STRONGkids) is a practical and easy nutritional risk screening tool that has been widely validated in several countries. Objective To examine the performance of STRONGkids for the early detection of hospital malnutrition in pediatric inpatients. Methods This cross-sectional study was conducted in the pediatric ward of Dr. Zainoel Abidin General Hospital, Banda Aceh, Indonesia. The pediatric inpatients' STRONGkids scores were calculated within 24 hours of admission. We used the chi-square test to compare the proportion of at-risk children based on STRONGkids scores with the prevalence of hospital malnutrition based on serial weight measurement. We also determined the sensitivity, specificity, as well as positive and negative predictive values of STRONGkids for detecting hospital malnutrition, with percentage of weight loss between admission and discharge as the gold standard. Result Out of 75 subjects, 48% were male. The hospital malnutrition prevalence was 29.3%. STRONGkids score was significantly associated with hospital malnutrition (P=0.023). The sensitivity, specificity, positive predictive value, and negative predictive value of STRONGkids for detecting hospital malnutrition was 77.3%, 54.7%, 41.4%, and 85.2%, respectively. Conclusion With its good sensitivity, the STRONGkids tool is effective in identifying those at risk of hospital malnutrition. In addition, with its high NPV, a “no-risk” score also effectively implies that the child is likely not to have hospital malnutrition.